Toward Low-Carbon Cement Production: The Role of Equipment Selection in CO₂ Reduction - Aisha Hafiza Saptomo (Jurnal Sains dan Teknologi, 2026)
The cement industry plays a strategic role in supporting economic development; however, its production processes contribute significantly to energy consumption, air pollution, and global CO₂ emissions. This study aims to formulate recommendations to enhance green manufacturing performance in an Indonesian cement company by identifying the most appropriate emission-reduction technology. CO₂ emissions were estimated using the Cement Sustainability Initiative (CSI) protocol equations to determine baseline emissions generated during production. A multi-criteria decision-making approach integrating Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied to evaluate alternative technologies, including carbon capture utilization and storage (CCUS), direct air capture, waste heat recovery (WHR), and modern burners. Data were collected from eight industry experts with more than ten years of professional experience. The results indicate that CCUS is the most preferred alternative, followed by WHR. Annual CO₂ emissions from the company range between 91 thousand and 1.9 million tons. Implementation of CCUS could reduce emissions by up to 17 kg per ton of cement, while WHR offers a reduction of up to 11 kg per ton. Investment requirements are estimated at USD 450 million for CCUS and USD 44.5 million per WHR unit.